Field study on effect of Hormonal Protocol on Treatment of Postpartum Anoestrus in Water Buffaloes of semi-arid region of Uttar Pradesh - Singh, Amit; Singh, DeepNarayan; Singh, Jai; Yadav, Sarvajeet (Indian Journal of Dairy Science, 2021)
Water Buffalo (Bubalus bubalis) is one of the premier productive animal and a major contributor to milk, meat, skin and draught power in our country. It is a better dairy animal in comparison to cattle in terms of better feed (roughage) conversion efficiency, greater resistance to diseases, and, higher milk fat percentage. But anoestrus is the most important cause of poor reproductive performance in buffaloes both in filed condition as well as in organized farm. The percentage of anoestrus is more in rural areas mainly due to malnutrition, lack of scientific knowledge and improper management practices causing huge economic losses to the farmers. Thus this study was conducted to test the effectiveness of these treatments in farmers field for treating anoestrus in buffaloes with PGF2Î± or GnRH protocol (ovsynch protocol) under the field conditions. A total of 36 animals were selected from different affected villages of Matura district with good body condition score (BCS >2.5), parity of two or above, healthy reproductive organs and history of minimum 6 months anoestrus problems after reaching the age of breeding or after calving or the last breeding were selected. The treated animals were examined per-rectal method. Among 36 treated buffaloes, 13 were found pregnant (36.11 %) and another 9 buffaloes had become cyclic with success rate of treatment was 61.11 %.